Estimation of salivary copper, zinc, iron and copper to zinc ratio in oral submucous fibrosis patients and its comparison with healthy individuals - Gitanjali Khulbe; Praveena Tantradi; Renuka Ammanagi; Sujata Byahatti (Journal of Indian Academy of Oral Medicine and Radiology, 2019)
Background: Trace elements have been found to be altered in oral submucous fibrosis (OSMF), an oral potentially malignant disorder which occurs as a result of a derangement in collagen metabolism. The literature on variation observed in the parameters of trace elements, in the saliva of OSMF patients and its correlation with the staging of OSMF, is limited. Hence, a case-control study was carried out to estimate the salivary concentrations of copper, zinc, and iron in OSMF patients. Materials and Methods: Out of the 120 patients enrolled, 60 OSMF cases and 60 healthy individuals were studied. Unstimulated whole saliva from each subject was centrifuged and the supernatant stored at -80°C. Laboratory analysis was done to estimate copper, zinc, and iron and the values were statistically analyzed. Results: The mean values of salivary copper, zinc, and iron were lower in OSMF cases than the controls and the mean copper to zinc ratio was higher in the cases, the differences being statistically insignificant. Conclusion: The chance differences that occurred in our study might have been due to lifestyle variations among the different subjects. Saliva may or may not be a representative of the changes seen in the trace element levels of OSMF patients.